Feasibility of Hydroprocessed Esters and Fatty Acids (HEFA) for Use as Automotive Fuels in the ASEAN Economic Blocs - Y. T. Teo; G. R. Mong; M. C. Chiong; C. T. Chong; J.-H. Ng (Journal of the Society of Automotive Engineers Malaysia, 2022)
Renewable diesel has been used as a substitute for diesel to resolve the depletion of crude oil. A data-driven modeling approach is conducted to study the production of potential and profitable Hydroprocessed Esters and Fatty Acids (HEFA) for diesel engine usage in ASEAN, ASEAN Plus Three (ASEAN+3), and ASEAN Plus Six (ASEAN+6) economic blocs. This study covers a total of 13 countries which comprises seven selected member states in ASEAN, three additional East Asian states in ASEAN+3, and another three extra Asia-Pacific countries in ASEAN+6. The profitable HEFA production at crude oil price = RM236/bbl is investigated under 3 different subsidy scenarios, namely no subsidy, partial subsidy (government subsidy), and full subsidy (government subsidy + market opportunity). The economic feasibility of HEFA in each country is classified into three main limiting factors which are the crude oil price, feedstock quantity, and Herfindahl-Hirschman Index in this model. In the no subsidy scenario, our model shows that the profitable HEFA production of ASEAN member states is uniformly limited by the crude oil price with only Myanmar being limited by feedstock quantity. Our model also shows that even though the neighboring Asia-Pacific countries are factored in, there will not be an increase in the profitable HEFA production at crude oil price = RM236/bbl under any subsidy scenarios. This study provides insights for governments to generate automotive policy about the cooperation of ASEAN member states with other countries through the ASEAN+3 and ASEAN+6 regarding renewable clean diesel energy.